Development of Electronic Commerce in Rural Retail Trade - Musayeva Shoira Azimovna (Research Parks Publishing LLC, 2021)
This article is devoted to the development of ways to improve trade services for the rural population. The authors propose modern organizational forms for the provision of trade services, proceeding from the typical demand of the rural population, which are based on the mechanisms of using e-commerce and electronic communications.